(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Rapid advances in wireless technology have been occurring in recent years. Nowadays, most research is conducted in the field of telecommunication. In the area of wireless communication, VANET is the fastest growing area. A mobile ad hoc network (MANET) is defined as a network that operates ad hoc on a mobile device (VANET) and which can be used to improve the road safety and also to improve the experience of passengers. VANET is comprised of vehicles to vehicles (V2V) and vehicles to infrastructure (V2I) communications supporting IEEE 802.11p wireless access technologies. ITS (Intelligent Transport Systems) are expected to improve road safety and motor traffic efficiency through this innovation in wireless communication. In order to make the VANET more robust, many issues must be addressed. An infrastructure based VANET might use mobile vehicles as sensors. By detecting, gathering, and disseminating real-time data about traffic conditions and road hazards, they can be able to detect, gather and share traffic information. This paper focuses on the history of VANETs, their challenges and potentials, as well as the way to preventing the long-awaited ITS.